Performance Study of Reproductive Performance in Female Bali Cattle in the Breeding Center of Konawe Selatan District - Dzulqarnain, Andi; Nafiu, La Ode; Pagala, Muhammad Amrullah (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
This study investigates the reproductive performance of Bali heifers in the breeding centers of Tinanggea, Palangga, Baito, and Buke Districts within the South Konawe District. Conducted from November 2022 to March 2023, the research was situated in Roraya Village, covering Asingi, Wonua Morini, Sambahule, Wulele, and Bomba – bomba. The sample comprised 24 Bali heifers, each having calved at least twice, from each sub-district, and 60 farmer breeders as respondents from each sub-district. Quantitative descriptive analysis was employed for data analysis, focusing on variables such as age at first parturition, postpartum mating (PPM), service per conception (S/C), and calving interval (CI). Supporting variables included age, education level, and livestock-raising experience. The research findings revealed the age of first calving ranged from 26.8 ± 0.2 to 29.6 ± 0.5 months, postpartum mating from 69.5 ± 0.4 to 96.5 ± 1.4 days, service per conception (S/C) from 1.0 ± 0.0 to 1.3 ± 0.5 times, and calving interval (CI) from 370.0 ± 0.5 to 405.0 ± 1.4 days. The results indicate that the reproductive performance of Bali heifers in the breeding centers of South Konawe Regency, particularly in Tinanggea, Palangga, and Buke, is still classified as very good. At the same time, Baito District shows a relatively efficient performance.